Foreign Direct Investment dan Risiko Politik di ASEAN - Olivia Tanaya; Rr. Savina Kanti Wilujeng; Irzameingindra Putri Radjamin (Politeknik Ganesha Medan, 2022)
Political risk is a risk that occurs due to political disturbances in a country that can affect its economy. This risk is one of the risks that investors consider when investing in a country. High political risks can create obstacles that potentially disrupt investors' business operations. This study aims to see the impact of political risk on Foreign Direct Investment (FDI) in the ASEAN region in 1996-2019 using panel data analysis with the best model, namely the fixed effect model (FEM). Sources of data in this study came from the World Governance Indicator (WGI) and World Development Indicator (WDI). The results of this study indicate that political risk as reflected in political stability and regulatory quality has a significant influence on FDI inflows in the ASEAN region. Political instability could make investors reluctant to invest in the country due to the concern about disturbances that will occur in the future. The role of governments in ASEAN countries is needed to maintain political stability and attract more foreign investors to invest in the ASEAN region. In addition, a country needs to have good regulatory quality so that investors do not experience obstacles in the early stages of investment. Complicated licensing and many regulations can be one of the obstacles in investing.